GRICE’S CONVERSATIONAL COOPERATIVE PRINCIPLES IN COMPETITIVE DEBATES - Teguh Adimarta (Widya Mandala Surabaya Catholic University, 2015)
This study examined the similarity and difference between Grice’s conversational principles and debate competition principles in the grand final of an East Java highshool debate competition. Most highschool debaters including the researcher perceived that there would be differences. Using the result of open-response questionnaires distributed to the adjudicator and 6 participants of the grand final of the competition, the researcher then inteviewed and discussed the debate transcript and the result of open-response questionnaires with some triangulators from the perspective of Grice’s conversational principles and competitive debate principles. The study reported that the maxims that are mostly interpreted differently in this debate are the violation of maxim of quantity and the observation of maxim of quality. This research finding also proved that the maxims that are mostly interpreted similarly in this debate are the violation of maxim of quality and the observation of maxim of quantity.